PENGARUH INTENSITAS ASET BIOLOGIS, PERTUMBUHAN PENJUALAN, KEPEMILIKAN MODAL ASING, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Jumaidi Rahman; Elin Erlina Sasanti; Kartikasari, Nungki (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2023)
This research aims to examine the influence of biological asset intensity, sales growth, foreign ownership, and company size on firm value in plantation companies listed on the Indonesia Stock Exchange (IDX) during the period of 2017-2021. The population in this study is all plantation companies listed on the IDX, using purposive sampling method with a sample size of 18 companies. The analysis method used in this study is multiple linear regression analysis. The results of the testing and discussion prove that biological asset intensity, sales growth, and foreign ownership have no significant effect on firm value. However, company size has a significant negative effect on firm value of plantation companies listed on the Indonesia Stock Exchange during the period of 2017-2021. This research also makes a practical contribution to companies and investors. This research can be used as a consideration in applying these research variables to help increase firm value and is also expected to assist investors in making the right decisions in investing.